IMPLEMENTASI PASAL 66 AYAT (1) HURUF B PERATURAN DAERAH PROVINSI KALIMANTAN BARAT NOMOR 1 TAHUN 2023 TENTANG ADAPTASI KEBIASAAN BARU DALAM PENCEGAHAN DAN PENGENDALIAN CORONA VIRUS DEISEASE 2019 (STUDI DI KANTOR BIRO HUKUM SEKRETARIAT DAERAH PROVINSI PONTIANAK) - NIM. A1011201111, AISYAH (Fakultas Hukum Universitas Tanjungpura, 2025)
ABSTRACT Prevention and control of Covid-19 is any form of effort made by the government, and/or the community to reduce the risks, problems, and overcome the adverse effects of Covid-19 to protect the community, and reduce the number of people infected to death, and to reduce the social impact of Covid-19.The formulation of the problem